Road Network and Household Food Security in Acholi Sub Region, Northern Uganda: A Pragmatic Perspective - Namubiru, Margaret; Nsambu Kijjambu, Fredrick; Ngaka, Willy; Rwakihembo, John (Journal of Developing Economies, 2022)
This study aimed at examining the relationship between road network and household food security in Acholi subregion, northern Uganda. Methodology: The study adopted a pragmatic paradigm, thus adopting a mixed methods approach. Quantitative data was collected from 384 respondents using a structured questionnaire while face-to-face interviews aided qualitative data collection. After data management and processing, Pearson correlation and standard regression were use for data analysis. Findings: It was observed that road network is positively and significantly associated with household food security. The study established that road network accounts for 10% of the variance in food security among households in Acholi subregion, northern Uganda. Unique contribution to practice and policy: Although there are conflicting views on the predictors of food security among households, the present study has confirmed thatroad network plays a critical role in influencing food security among households in Acholi subregion, Northern Uganda, thus serving its purpose.
Keywords: Road network; Household; Food Security